REGIONAL DEVELOPMENT FEATURES AND TECHNOLOGICAL SUPPLY INDICATORS OF THE BEEKEEPING INDUSTRY IN THE REGION - Farmonov, Jonibek Ziyodullayevich; Bazarov , Sanjar Safarovich (THE INNOVATION ECONOMY, 2026)
This study analyzes the economic and ecological impact of climate change on the beekeeping industry. It is substantiated that abrupt changes in temperature, drought and disruption of the precipitation regime negatively affect nectar flow, flower phenology and the viability of bee colonies. The study shows the inadequacy of traditional management methods in ensuring production sustainability, and highlights the need to introduce digital monitoring systems, innovative technologies and adaptation strategies. It also proposes ways to increase economic efficiency and ensure sustainable development of the industry by forming a climate-adapted beekeeping system.